Determination of sea-floor seepage locations in the Mississippi Canyon. (January 2015) - Crooke, Emma; Talukder, Asrar; Ross, Andrew; Trefry, Christine; Caruso, Michael; Carragher, Peter; Stalvies, Charlotte; Armand, Stephane
Abstract: The ephemeral nature of marine oil and gas seepages and their complex trajectories in the water column make seep sampling difficult and costly. Here we report on how active natural seepage can be detected and located in the water column and at the sea bed in real time through the integration of marine X-band radar, synthetic aperture radar, field observations, high resolution single beam acoustic methods, and meta-ocean data from the marine environment with a simple bubble rise model. The extent of predictions made using a bubble rise model narrow down the likely seafloor origin point of an observed surface feature to within a radius of 630 m within which clusters of acoustic contacts were detected. Use of averaged deep current velocities and directions narrows the radius to 130 m, and use of a smaller established range of bubble rise speeds from the Gulf of Mexico can narrow the predicted seafloor origin radius further to 16.5 m. These results are useful for focussing detailed sea bed search patterns for natural seepage and are also suggestive of a seep system with complex water column trajectories associated with Biloxi Dome in the Gulf of Mexico. Highlights: Survey undertaken to characterise natural seepage at Biloxi Dome, Gulf of Mexico. Marine oil slicks observed with both synthetic aperture and ship-borne X-band radar. Model uses local current and bubble rise information to predict sea-floor origin. Predicted sea-floor origin of observed slicks narrowed down to within 630 m radius.